ПОЖААААЛУЙСТА, ПОМОГИТЕ.

ВСЕ ВНУТРИ

    x^2+3x-10=0

    y-12+4*sqrt(y)=0

    x^2+3x-6=4>0

    y2=(40-32)/2=4

    x3=(-3+7)/2=2

    x^2+3x-42=0

    x1=(-3+sqrt(177))/2

    D=9+168=177

    y1=(40+32)/2=36

  • x^2+3x-18+4*sqrt(x^2+3x-6)=0

    y^2-40y+144=0

    x^2+3x-6=36>0

    D=9+40=49=7^2

    Вводим замену x^2+3x-6=y

    16y=144-24y+y^2

    x2=(-3-sqrt(177))/2

    x4=(-3-7)/2=-5

    Ответ: (-3+sqrt(177))/2; (-3-sqrt(177))/2; 2; -5

  • 4*sqrt(y)=12-y

    D=1600-4*144=1600-576=1024=32^2